Bailey’s industrial oil & fat products (vol.6) - Bailey, Alton Edward (John Wiley & Sons, 2005)
The sixth volume on nondible uses of fats and oils has new articles on biodiesel, hydrolic fluids, lubricants, inks, as well as pharmaceutical and cosmetic uses of lipids. An articles on the use of soybean oil in edible film and adhesive production is also included